2006
DOI: 10.1016/j.bbabio.2006.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Acclimation of mesophyll and bundle sheath chloroplasts of maize to different irradiances during growth

Abstract: The regulation by light of the photosynthetic apparatus, and composition of light-harvesting complexes in mesophyll and bundle sheath chloroplasts was investigated in maize. Leaf chlorophyll content, level of plastoquinone, PSI and PSII activities and Lhc polypeptide compositions were determined in plants grown under high, moderate and low irradiances. Photochemical efficiency of PSII, photochemical fluorescence quenching and non-photochemical fluorescence quenching over a range of actinic irradiances were als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 47 publications
0
37
1
Order By: Relevance
“…In addition, the structure of the BS chloroplasts was suggested not to be influenced by the light intensity and was similar in plants grown in full tropical sunlight or under low irradiance (46). In contrast, our recent results have shown that various light growth conditions may alter polypeptide composition of the BS thylakoids of maize (14).…”
Section: Discussioncontrasting
confidence: 43%
See 3 more Smart Citations
“…In addition, the structure of the BS chloroplasts was suggested not to be influenced by the light intensity and was similar in plants grown in full tropical sunlight or under low irradiance (46). In contrast, our recent results have shown that various light growth conditions may alter polypeptide composition of the BS thylakoids of maize (14).…”
Section: Discussioncontrasting
confidence: 43%
“…PSII activity was assayed spectroscopically by measuring the photoreduction rate of the artificial electron acceptor 2,6-dichlorophenolindophenol, as described in Ref. 14 Blue Native-PAGE and Immunodetection-Protein solubilization and BN-PAGE were performed according to Schägger et al (29) and Kügler et al (30) with slight modifications. Thylakoid membranes (50 g of Chl) were sedimented at 7,000 ϫ g for 5 min at 4°C and resuspended in a buffer composed of 5 mM EACA, 50 mM imidazole-HCl, pH 7, 50 mM NaCl, 0.5 mM EDTA.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other than that, all plant ages that involved in this study is one year. Before experimental were conducted, all plants involved must be assimilated with the indoor environment for at least two months, as recommended by Drozak and Torpy [29,26]. In assimilation process, allowing plants to tolerate with indoor environment, where lighting and temperature is different compared to their original habitation.…”
Section: Indoor Plant Materialsmentioning
confidence: 99%